Informative priors on fetal fraction increase power of the noninvasive prenatal screen. (August 2018) - Xu, Hanli; Wang, Shaowei; Ma, Lin-Lin; Huang, Shuai; Liang, Lin; Liu, Qian; Liu, Yang-Yang; Liu, Ke-Di; Tan, Ze-Min; Ban, Hao; Guan, Yongtao; Lu, Zuhong
Abstract Purpose Noninvasive prenatal screening (NIPS) sequences a mixture of the maternal and fetal cell-free DNA. Fetal trisomy can be detected by examining chromosomal dosages estimated from sequencing reads. The traditional method uses theZ- test, which compares a subject against a set of euploid controls, where the information of fetal fraction is not fully utilized. Here we present a Bayesian method that leverages informative priors on the fetal fraction. Method Our Bayesian method combines theZ- test likelihood and informative priors of the fetal fraction, which are learned from the sex chromosomes, to compute Bayes factors. Bayesian framework can account for nongenetic risk factors through the prior odds, and our method can report individual positive/negative predictive values. Results Our Bayesian method has more power than theZ- test method. We analyzed 3, 405 NIPS samples and spotted at least 9 (of 51) possibleZ- test false positives. Conclusion Bayesian NIPS is more powerful than theZ- test method, is able to account for nongenetic risk factors through prior odds, and can report individual positive/negative predictive values.